The Importance of Skeletal Muscle Oxygenation Kinetics for Repeated Wingate-Based Sprint Performance - Andrew Usher; John Babraj (Muscles)
Boxing is a sport that has a high level of oxygen use within the Rectus Femoris muscle, with recovery between rounds important to subsequent performance. The study aimed to determine muscle oxygen use in male and female professional boxers in response to a repeated sprint stimulus. 10 male (age: 26 ± 5 years, height: 177 ± 4 cm, weight: 72 ± 6 kg) and 6 female (age: 29 ± 4 years, height: 173 ± 2 cm, weight: 73 ± 4 kg) professional boxers took part. Participants attended a single session where a Moxy near-infrared monitor was placed on the rectus femoris muscle of both legs. Participants completed 2 × 30 s Wingate-based sprint efforts with a 60 s active recovery (maintaining 60 rpm against 50 W resistance). Skeletal muscle oxygenation was recorded throughout. Significant differences were found in peak power, average speed and rate of fast desaturation between males and females (p < 0.001) in both sprints. There was a significant difference in males and females for the rate (sprint 1M: −5.6 ± 1.2%.s−1, 1F: −2.3 ± 1.9%.s−1, p < 0.05; sprint 2M: −4.2 ± 1.1%.s−1, 2F: −1.5 ± 0.9%.s−1, p < 0.05) and duration of fast desaturation (sprint 1M: 6.1 ± 1.3 s, 1F: 3.7 ± 2.8 s, p < 0.05; sprint 2M: 7.3 ± 1.6 s, 2F: 4.5 ± 1.0 s, p < 0.05) in both sprints. This study demonstrates that male professional boxers have a significantly different oxygen use and recovery in response to a high-intensity stimulus compared to female boxers. In both male and female boxers, the ability to perform subsequent high-intensity activity is dependent on the quality of the recovery from the initial high intensity activity. Therefore, there is a greater need to focus training to improve recovery kinetics in boxing.